Elevated Expression of the Testis-specific Gene WBP2NL in Breast Cancer - Nourashrafeddin, Seyedmehdi (Biomark Cancer, 2015)
Breast cancer is one of the most common causes of cancer death in women; therefore, the study of molecular aspects of breast cancer for finding new biomarkers is important. Recent studies have shown that WW domain-binding protein 2 (WBP2) is important for the oncogenic property of breast cancer. WWP2 N-terminal-like (WBP2NL) is a testis-specific signaling protein that induces meiotic resumption and oocyte activation events. Our previous study revealed that WBP2NL gene expression is elevated in actively dividing cells and it might be associated with cellular proliferation and tumorigenic process. However, the clinical relevance and importance of WBP2NL gene in cancer has not been understood yet. Therefore, we were interested in analyzing the expression of WBP2NL gene in human breast cancer tissues and breast cancer cell lines, for the first time. We used reverse transcription-polymerase chain reaction (RT-PCR) and semi-nested RT-PCR to evaluate the expression of WBP2NL in malignant breast cancer and adjacent noncancerous tissue (ANCT) samples, as well as MCF-7 and MDA-MB-231 cell lines. The WBP2NL gene was expressed in 45 out of 50 (90%) breast cancer tissues and overexpressed in the MDA-MB-231 cell line. We suggest that WBP2NL may play roles in breast cancer activation maybe through binding to a group I WW domain protein. The elevated expression of WBP2NL gene in breast cancer and MDA-MB-231 cell line leads us to suggest that WBP2NL might be considered as a novel prognostic factor for early diagnosis of breast cancer.